Correlation Between The Adequacy Of Protein And Vitamin Intake With The Incidence Of Anemia In Pregnant Women - Dwi Nastiti Rahayu; Siti Sulandjari; Amalia Ruhana; Satwika Arya Pratama (Poltekkes Kemenkes Mataram, 2024)
Background: Nutritional deficiencies in pregnant women can affect fetal growth and development and cause anemia during pregnancy. Anemia can be characterized by hemoglobin concentration lower than a normal boundary. This study investigates the correlation between the adequacy of protein, vitamin C, vitamin A, vitamin B12, and folic acid intake and the incidence of anemia in pregnant women at Ngoro Health Center.Research Methods: The research is analytically observational, using a cross-sectional design. The study subjects were 52 pregnant women using a purposive sampling technique. Anemia in pregnant women was obtained from the results of hemoglobin level checks recorded in the Antenatal Care (ANC) visit logbook. Meanwhile, the adequacy of protein, vitamin C, vitamin A, vitamin B12, and folic acid intake was obtained from interviews using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) form. The statistical correlation between categorical variables was analyzed using the chi-square test.Research Result: The study found that out of 52 pregnant women, it was known that the pregnant women's adequacy level of intake for protein (65.4%) was classified as less, vitamin C (94.2%) was classified as good, vitamin A (98.1%) was classified as good, vitamin B12 (69.2%) was classified as good, and folic acid (76.9%) was classified as good. Statistical test results showed that the adequacy of protein intake (p 0.001), vitamin B12 (p 0.035), and folic acid (p 0.021) correlates with the incidence of anemia in pregnant women.Conclusion: Based on this study, there is a significant correlation between the adequacy of protein, vitamin B12, and folic acid intake, but no correlation between the adequacy of vitamin C and vitamin A intake with the incidence of anemia in pregnant women in the working area of Ngoro Health Center, Mojokerto Regency. Pregnant women are expected to pay more attention to their nutrition intake during pregnancy.